Qualidade de ovos de poedeiras comerciais alimentadas com óleos essenciais como aditivo alternativo - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Antimicrobials, in general, have been used as additives in poultry feed both to maintain health, therapeutic and prophylactic use, and to increase their performance, used as growth promoters. Therefore, the objective was to evaluate the quality of poultry eggs fed diets containing essential oils and growth-promoting additives. Birds' eggs housed in a farm located in the Bela Vista de Goiás region, of the Lohmann Brown lineage at 60 weeks of age, were evaluated. The design used was entirely random in a 3 x 6 factorial scheme (types of feeding x collection weeks), with 15 repetitions of an egg, totaling 270 experimental units. The types of feed were the premix plus essential oils of cloves and thyme; premix containing the growth promoter called Halquinol and standard mineral and vitamin premix (control). The variables analyzed were: albumen height, egg weight, Haugh Unit, yolk color and shell weight. The use of essential oil of thyme and clove in the laying diet proved to be effective in egg quality, for the variables egg weight, Haugh unit and yolk color under the evaluated conditions.
Keywords: Alimentos saudáveis; Antimicrobianos; Carvacrol; Eugenol; Ingredientes alternativos; healthyfood; Antimicrobials; Carvacrol; Eugenol; alternative ingredients; CIENCIAS AGRARIAS